Evaluation of the Antifungal Activity of Ethanolic Extract of Curcuma longa L. Against Candida albicans - Luza-Montero, Silvia C. (2025)
Objective: Candida albicans is an opportunistic fungus responsible for persistent oral and endodontic infections, whose prevalence has increased due to resistance to conventional antifungal treatments. In this context, natural compounds with antifungal activity represent a promising alternative. This study aimed to evaluate the antifungal activity of the ethanolic extract of Curcuma longa L. (EECl) against C. albicans ATCC 10231. Materials and Methods: The antifungal activity was assessed using the agar well diffusion method. EECl was tested at concentrations of 100, 50, 25, and 12.5 mg/mL. Nystatin was used as the positive control. After inoculation of the fungal strain on YPG agar and loading of the wells with the corresponding solutions, plates were incubated and inhibition zones were measured in millimeters. Results: All concentrations of EECl showed antifungal activity, with larger inhibition zones observed at higher concentrations. Statistically significant differences were found between groups (p = 0.040). However, post hoc analysis revealed no significant differences among the 25, 50, and 100 mg/mL concentrations (p = 1.000), suggesting that increasing the concentration beyond 25 mg/mL does not substantially improve antifungal activity. The 12.5 mg/mL group showed significantly lower activity compared to nystatin (p = 0.026). Conclusion: EECl demonstrated antifungal activity against C. albicans, though nystatin remained more effective. These results support the potential use of Curcuma longa L. as a natural antifungal agent, warranting further research.